Vacuolar Protein Sorting Genes in Parkinson's Disease: A Re-appraisal of Mutations Detection Rate and Neurobiology of Disease - Gambardella, Stefano; Biagioni, Francesca; Ferese, Rosangela; Busceti, Carla L.; Frati, Alessandro; Novelli, Giuseppe; Ruggieri, Stefano; Fornai, Francesco (Frontiers in Neuroscience, 2016)
Mammalian retromers play a critical role in protein trans-membrane sorting from endosome to the trans-Golgi network (TGN). Recently, retromers have been linked to Parkinson's Disease (PD) since the identification of the variant p.Asp620Asn in VPS35 (Vacuolar Protein Sorting 35) as a cause of late onset PD. This variant causes a primary defect in endosomal trafficking and retromers formation, which represent critical steps in the molecular mechanisms of disease. Other slightly penetrant and mildly deleterious mutations in VPS genes have been reported in both sporadic and familial PD. Therefore, understanding the actual prevalence of the whole range of VPS gene mutations is key to understand the relevance of retromers impairment in PD. This scenario indicates a plethora of mutations occurring in different pathways (autophagy, mitophagy, proteasome, endosomes, protein misfolding) all converging to cell clearing systems. This may explain how genetic predispositions to PD may derive from slightly deleterious mutations when combining with heterogeneous environmental factors. This manuscript is a re-appraisal of genetic data produced in the last five years redefining the prevalence of VPS mutations in PD. The prevalence of p.Asp620Asn in VPS35 is 0.286 of familial PD. This data increases up to 0.548 considering mutations affecting all VPS genes, thus representing the second most frequent autosomal dominant PD genotype. This high prevalence, joined with increased awareness of the key role of retromers alterations in PD, strongly candidate environmentally-induced VPS alterations as key molecular mechanisms in the genesis of PD. rations as key molecular mechanisms in the genesis of PD.